Soft tissue sarcoma - Aguiar, Alberto; Delgado, Bolívar; Aliano, F (Cirugía del Uruguay, 2021)
In this. paper we find twenty clinical observations of soft tissue sarcomas and their evolution treated by the authours and another small group of surgeons, with similar principles of diagnosis and treatment. The histogenetic classification of this kind of tumors is followed by an analysis of its clinical anatomic and evolutive characteristics. Classification into several groups is accompanied by therapeutic directives. Finally we find the problem of recurrences, with more serious prognosis, and their treatment.